The Implementation of the SDGs in North Korea: Realities and Problems - 이종운 (Korean Journal of Social Quality, 2023)
The purpose of this paper is to examine the status of North Korea’s implementation of the Sustainable Development Goals (SDGs) and outline the challenges and difficulties that North Korea has faced in implementing them. Stringent international sanctions and the pandemic-related border closure notwithstanding, North Korea expressed willingness to the implementation of the SDGs and conducted a Voluntary National Review (VNR) in July 2021. As shown in the VNR report, a distinctive feature of North Korea’s implementation of the SDGs is its establishment of “country specific SDGs” with considerable modifications and adaptations to their contents. This paper examines the characteristics of SDG implementation in North Korea and identifies the limitations of its SDG implementation. The paper also explores socioeconomic and environmental situations related to the SDGs through a review of North Korean statistical data and SDG indicators. North Korea’s implementation of the SDGs has faced economic and geopolitical challenges under international sanctions. The border closure since 2020 has adversely affected the livelihoods of ordinary North Koreans and derailed the process of implementing the SDGs and related activities. This paper demonstrates North Korea’s urgent need for international assistance in improving the humanitarian situation and advancing the implementation of the SDGs. KCI Citation Count: 0